PELAKSANAAN PROGRAM KEMITRAAN DAN BINA LINGKUNGAN (PKBL) PADA PT. PLN (PERSERO) AREA SEMARANG - Rizky Dewi Anggorowati, Budiharto, Siti Mahmudah (Diponegoro Law Journal, 2012)
Partnership and Community Development is one of CSR that must be implemented State-Owned Enterprises. In Article 2 of the state, requiring the State-Owned Enterprises to provide guidance and assistance to the economically weak entrepreneurs, cooperatives and communities. Based on this background, the authors do legal research entitled Implementation of the Partnership and Community Development at PT. PLN (Persero) Semarang area with problems: 1). How is the implementation of the Partnership and Community Development at PT. PLN (Persero) Semarang area, 2). What are the obstacles that arise in implementing the Partnership and Community Development at PT. PLN (Persero) Semarang area, and how to overcome them. The method used is the juridical empirical research using descriptive analytical specifications. The type of data in this study is primary data and secondary data. The method of data collection using interviews with a purposive sampling technique. The method of data analysis using qualitative methods. The results of the study implementation of the Partnership and Community Development at PT. PLN (Persero) Semarang area, governed by the Board of Directors Decision PT. PLN (Persero) No.336.K/DIR/2007 of Standard Operation Procedure (SOP) Implementation Program Partnership with Small Business Enterprises and Community Development Program/​​Environmental Empowerment Program Participation (PKBL/P3L), in accordance with what is stipulated in minister of state-owned enterprises No.:Per-05/MBU/2007 about SOE Partnership Program with the Small Business and Community Development Program. Obstacles that arise in the implementation of CSR is that many of them are stuck in the Patronage Partners timeliness principal payment and loan administration services, the number of proposals, but funds are limited. Handling cases of bad loans through rescheduling (rescheduling). While the proposals and deserves to receive aid distribution fund PBL but not sufficient, be included in the PBL next semester.